Development and experiment of the intelligent control system for rhizosphere temperature of aeroponic lettuce via the Internet of Things - Mohamed, Tarek Mahrous Korany; Gao, Jianmin; Tunio, Mazhar (International Journal of Agricultural and Biological Engineering, 2022)
Currently, in the conventional aeroponic system the collection of data for crop performance is quite slow, whereas such data are typically collected manually. Correspondingly, the root zone temperature is one of the most important factors affecting plant growth in aeroponics cultivation. This study aimed to obtain temperature and relative humidity data inside an aeroponic system based on the Internet of things (IoT) and automatically cool the root zone using a novel low-cost effective technique for cooling via a cooling fan connected to the Arduino board. The results revealed that the newly designed system could monitor and record the data in real-time on an internet server per hour. Furthermore, the temperature and humidity data can be displayed on the smartphone application, and be sent to the personal email weekly as an excel sheet. This system was able to maintain the temperatures inside the roots chamber between 28.7°C-29.2°C while the maximum external temperature was 38.1°C, and the average temperature in the traditional aeroponics system was fluctuating between 29.5°C-31.5°C. The newly automated cooling system root zone system of this study showed an optimization of lettuce growth characteristics. It significantly increased the lettuce absorbance of inorganic nutrients such as N, P, and K by 45.5%, 66.6%, and 45.0%, respectively, and revealed an increment of fresh weight, total chlorophyll, ascorbic acid, total carbohydrate, and total amino acids by 131.0%, 26.2%, 41.9%, 30.7%, 6.2%, respectively in comparison with the conventional aeroponic system. Therefore, this study may play a significant role in the aeroponic monitoring and control, for providing more suitable growth parameters and achieving the least human interaction.Keywords: aeroponics, IoT, rhizosphere temperature, lettuce, intelligent control systemDOI: 10.25165/j.ijabe.20221503.6530Citation: Mohamed T M K, Gao J M, Tunio M. Development and experiment of the intelligent control system for rhizosphere temperature of aeroponic lettuce via the Internet of Things. Int J Agric & Biol Eng, 2022; 15(3): 225–233.